Development of Pictorial Textbook for Arabic Speaking Skill in Islamic Studies Program - Muhammad Ainur Roziqi (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
This research offered solutions and answers to the textbook problems of Arabic learning in the Arabic language development program at Islamic Studies Faculty of Universitas Muhammadiyah Malang. The development of textbooks was done by adding pictorial explanations to the relevant vocabulary, also the learning material developed according to the expected profession. In addition, interactive exercises and themes were adapted to student interests and program goals. This study used ADDIE as a research and development model to produce innovative study, productive, and meaningful. The results of the validity tests were as follows: language validation tests show a percentage of 90%. The result of content validation was 92%, design validation result was 86%, while the result of lecturer validation was 95%. From these data, it can be concluded that the textbook was valid. Similarly, the effectiveness test by using (T-Test) showed effective results so that textbooks that had been developed were feasible to use.